Excavated endoexoenteric form of lymphoma - Pekanan, P.; Nirapathopongporn, S.; Chaovisit, S.; Siriwongpairat, P. (The ASEAN Journal of Radiology, 2023)
The principal radiologic features of lymphoma of the small bowel, as described by Marshak and colleagues (1) were multiple nodular defects, an infiltrating form, a polypoid form (intussuscepting), an endoexoenteric form with excavation and fistula formation, and a predominantly mesenteric invasive form with extraluminal masses. Aneurysmal dilatation has been considered the major radiologic finding in some reports (2). The infiltrating form was the most frequent radiologic finding, closely followed by the cavitary form (3). Replacement of the muscularis and destruction of the autonomic nerve plexus by lymphoma may cause the bowel wall to give way and bulge focally. Aneurysmal dilatation tends to involve predominantly the unsupported, antimesenteric side of a small bowel segment. The contour may revert to normal after treatment; however, perforation is a life-threatening complication (4). For this reason, complete resection should be attempted whenever possible before chemotherapy (5). Focal infiltration may lead to localized perforation into a sealed-off space, usually between the leaves of the mesentery. This cavitary form of non-Hodgkin's lymphoma usually denotes a primary small bowel origin. The irregular contour of the excavation, its relation to the mesenteric border of a small bowel loop, the fact that it contains air and debris and the generally thin soft tissue space separating it from adjacent bowel, distinguish cavitary lymphoma from a barium-containing cavity within an exoenteric leiomyosarcoma. An aneurysmal dilatation or sacculation may superficially resemble the lymphomatous cavity; it is, however, likely to involve the antimesenteric side of a bowel segment and to be in continuity with the bowel lumen proximally and distally. Cavitary lymphoma requires surgical excision, at times of a considerable extent of the involved bowel.